Antibody effectors: Monocytes as mediators of immunoglobulin G-dependent effector functions - Biburger, Markus; Nimmerjahn, Falk (BioSpektrum, 2012)
Antibodies carry out effector functions either directly or by binding of immune complexes to cellular Fc-receptors. Here we focussed on two mouse models: a model for immune-thrombocytopenia, where platelets are depleted by injection of anti-platelet antibodies, and a model for lymphoma treatment, where B-cells are depleted by CD20-specific antibodies. In both cases we found the activating Fc-receptors FcγRI and IV to be essential for IgG activity. © Springer-Verlag 2012.
Keywords: Antikörper; Antibodies; Effector functions